FREQUENCY AND DETECTION OF EXTENDED SPECTRUM BETALACTAMASE IN ESCHERICHIA COLI AND KLEBSIELLA PNEUMONIAE: A STUDY AT LADY READING HOSPITAL PESHAWAR - Bari, Fazli; Shah, Hamidullah; Wazir, Rubina (Journal of Postgraduate Medical Institute, 2016)
Objectives: To detect extended spectrum beta lactamase in E. coli and Kleb-siella pneumonia in bacterial cultures and its frequency at Lady Reading Hos -pital, Peshawar. Methodology: This cross sectional analytical study was conducted at LRH between June 2013 to December 2013, a total of 1037 bacterial isolates in-cluding 614 E. coli and 423 of Klebsiella pneumoniae were evaluated. All cas-es were subjected to double disc diffusion method for ESBL detection using amoxacilln-clavulanic acid and a third generation cephalosporin as all ESBLs are hydrolysed by clavulanic acid. The data were analysed using SPSS-16. Results: Patients' mean age was 40 years. Out of 1037 cases,592 (55%) were males and 445 (45%) were females. Of these, E. Coli were 614 (59.2% ) and K. Pneumoniae were 423 ( 40.8% ).Frequency of ESBL positivity in E. coli iso-lates was 264 (43%) and in Klebsiella pneumonia isolates was 231 (54.6%). Frequency of ESBL in pus was 34.3%(152/395),in urineit was 31.8%(141/368), in blood it was 28.6%(127/233) and in sputum it was 5.1% (23/41).Unit-wise frequency of ESBL was surgical & allied 24.6%( 109/283), medical and allied 21.4% (95/241), paediatrics 18.5%(82/203), obstetrics &gynaecology23.2% (103/178) and outpatients 12.1 %(54/132). No significant correlation between ESBL positivity and age, gender, unit or specimen was found. Conclusion: ESBL positive isolates of E. coli and K. pneumoniae account for a very high percentage of hospital-acquired infections. These results should be considered while prescribing penicillins and cephalosporins for treating gram-negative acquired infections.